Circulation of human metapneumovirus among children with influenza‐like illness in Wuhan, China. Issue 5 (7th January 2016) - Kong, Wenhua; Wang, Ying; Zhu, Honghao; Lin, Xinming; Yu, Bin; Hu, Quan; Yang, Xiaobing; Guo, Deyin; Peng, Jinsong; Zhou, Dunjin
Abstract : Human metapneumovirus (HMPV) is a worldwide distributed pathogen of the respiratory tract. The objectives of this study were to identify HMPV infections among children with influenza‐like illness (ILI) in Wuhan and to assess circulation patterns and molecular diversity of HMPV in this area. From July 2008 to December 2013, a total of 3, 883 throat swab samples were collected from ILI outpatients under 16 years old. HMPV RNA was detected in 171 samples (4.40%). All the four subtypes of HMPV were identified, among which A2 was the most common subtype (61/145, 42.1%), followed by B1, B2, and A1. During the study period, HMPV circulation presented a biennial alternation between high and low incidence in Wuhan and the seasonal peak also shift between winter and spring in two continuous seasons. Subtype A2, B1, and B2 co‐circulated during the study period, with genotype A prevailing in epidemic season 2008–2009 and 2012–2013, and genotype B prevailing during other periods. This large‐scale analysis of HMPV prevalence in ILI outpatient children improves the understanding of local HMPV circulation patterns and provides molecular epidemic evidence for comparative analysis of HMPV infection. J. Med. Virol. 88:774–781, 2016 . © 2015 Wiley Periodicals, Inc.